Molecular insights into pancreatic cysts: navigating diagnosis and precision management - Rudy El Asmar; Nazih Bizri; Nikhil Vaishnav Tirukkovalur; Adam Tcharni; Navya Dasyam; Samer AlMasri (Exploration of Digestive Diseases)
Pancreatic cystic lesions are frequently found incidentally on cross-sectional imaging and are broadly classified into mucinous and non-mucinous cysts. While some exhibit benign behavior, others have a malignant potential and are considered noninvasive precursors of pancreatic ductal adenocarcinoma. Guidelines from various societies propose risk stratification based on morphologic features and cyst fluid analysis. Fluid analysis through EUS-guided fine needle aspiration contributes to improved classification and recently, targeted DNA or RNA-based next generation sequencing is emerging as a critical investigation tool for diagnostic confirmation and risk stratification of pancreatic cysts. Each of these modalities has specific strengths and limitations, highlighting the need for a multi-modal approach for comprehensive assessment to guide clinical decision making. In this perspective, we aim to provide a thorough clinicopathologic framework for diagnosing and risk stratifying pancreatic cysts encompassing imaging findings, cyst fluid analyses, and next generation sequencing.